IMPLEMENTASI MANAJEMEN STRATEGIK DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SMK MIFTAHUL HUDA AL HUSNA KOTA TASIKMALAYA - Siti Malihah, Iim; Wartim; Abdussalam, Aam (An-Nahdliyyah: Jurnal Studi Keislaman, 2024)
institutions need management to ensure effective and efficient education. One of the ways this can be realized is by having quality teaching staff. In reality, there are still inadequately qualified teaching staff which has an impact on school quality. Thus, strategic management is needed to overcome this. The aim of this research is to determine the implementation of strategic management, the quality of teaching staff, and the implementation of strategic management in improving the quality of teaching staff at Miftahul Huda Al Husna Vocational School, Tasikmalaya City. The research uses a qualitative approach. Data was collected through observation, interviews and documentation. The analysis technique uses data reduction steps, data presentation, and drawing conclusions. The research results show that: 1) the implementation of strategic management runs quite optimally through activities a) strategic planning including formulating the school's vision, mission and goals, internal and external analysis using SWOT analysis, and making short, medium and long term plans. b) strategic implementation includes having school policies, providing motivation to teaching staff, and allocating resources, c) strategic evaluation by supervising all school programs, monitoring the learning process, and providing direction. 2) quality of staff, a) pedagogical competence by compiling, implementing and evaluating learning, b) personality competence, namely being a role model for students, and 3) social competence by communicating with students, fellow students, parents/guardians of students and the community, and d) professional competence is visible from mastery of the subjects taught. (3) the implementation of strategic management at Miftahul Huda Al Husna Vocational School, Tasikmalaya City is quite optimal so that it has an impact on the quality of teaching staff. However, there are still several factors inhibiting teaching staff, not all of them are linear and there is a lack of certified teaching staff. Supporting factors include the enthusiasm and cooperation of teaching staff in implementing strategic management.